2021
DOI: 10.1186/s40748-021-00130-w
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine utilisation and maternal complications during antenatal care among women in Bulilima, Plumtree, Zimbabwe

Abstract: Background As part of the expectation enshrined in the Sustainable Development Goals, countries are expected to ensure maternal health outcomes are improved. It follows that under ideal circumstances, pregnant women should deliver safely without complications, neonatal, and maternal mortality. This paper analyses the relationship between traditional medicine utilisation and maternal complications during antenatal care among women in Bulilima, Plumtree, Zimbabwe. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…28,29 The study noted that traditional practitioners could chase away evil spirits that usually make nurses have negative attitudes towards pregnant women affecting the delivery process. Some mechanisms of chasing evil spirits from the study are similar to studies conducted by Aziato et al 30 and Mudonhi and Nunu 31 who highlighted anointing oil, blessed water, sticker, blessed white handkerchief, blessed sand, Bible and Rosary. Furthermore, studies conducted in Islamic tradition revealed that prayer is a weapon to chase away evil spirits.…”
Section: Discussionsupporting
confidence: 86%
“…28,29 The study noted that traditional practitioners could chase away evil spirits that usually make nurses have negative attitudes towards pregnant women affecting the delivery process. Some mechanisms of chasing evil spirits from the study are similar to studies conducted by Aziato et al 30 and Mudonhi and Nunu 31 who highlighted anointing oil, blessed water, sticker, blessed white handkerchief, blessed sand, Bible and Rosary. Furthermore, studies conducted in Islamic tradition revealed that prayer is a weapon to chase away evil spirits.…”
Section: Discussionsupporting
confidence: 86%
“…In spite of widespread national commitment to reducing maternal deaths and improving reproductive health in Zimbabwe (Mlambo et al, 2013), little information is available on the use of herbal medicines or CAM by pregnant women in Zimbabwe. Previous studies by Mawoza et al (2019) and Mudonhi & Nunu (2021) collected data on herbal medicines used during Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas / 633 pregnancy in Zimbabwe by interviewing pregnant women while the current study interviewed herbalists, traditional birth attendants, traditional healers, assistant traditional healers and herbal medicine vendors. Therefore, this study aimed at documenting CAM and herbal medicines used by pregnant women in Makoni district, Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no country should be left with a MMR of greater than double the global average [ 1 ]. For Zimbabwe, a country with one of the worst MMRs globally, estimated to be in excess of 450 maternal deaths (MDs) per 100 000 live births [ 2 ], a lot of work needs to be done to make reasonable progress towards attaining SDG3. Identifying the contributory factors and putting in place mitigatory measures is a key step in making progress towards resolving a challenge.…”
mentioning
confidence: 99%